2012
DOI: 10.1007/s12192-011-0298-y
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus-mediated expression of the HO-1 protein within MSCs decreased cytotoxicity and inhibited apoptosis induced by oxidative stresses

Abstract: The capacity of mesenchymal stem cells (MSCs) to survive and engraft in the target tissue may lead to promising therapeutic effects. However, the fact that the majority of MSCs die during the first few days following transplantation complicates cell therapy. Hence, it is necessary to strengthen the stem cells to withstand the rigors of the microenvironment to improve the efficacy of cell therapy. In this study, we manipulated MSCs to express a cytoprotective factor, heme oxygenase-1 (HO-1), to address this iss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 16 publications
1
39
0
Order By: Relevance
“…Cellular morphology and proliferation, in-vitro differentiation, and surface molecule characterization of our results all demonstrated that Ad/HO-1 did not alter the biological properties of BMMSCs, which was in agreement with previous studies [9, 43, 45]. Immunocytochemical staining revealed that the red fluorescence intensity in the cytoplasm was higher, while western blot analysis showed more HO-1 expression in Ad/HO-1/BMMSCs than in BMMSCs and in Ad/BMMSCs, indicating that the HO-1 gene was successfully overexpressed in the cytoplasm of Ad/HO-1/BMMSCs.…”
Section: Discussionsupporting
confidence: 93%
“…Cellular morphology and proliferation, in-vitro differentiation, and surface molecule characterization of our results all demonstrated that Ad/HO-1 did not alter the biological properties of BMMSCs, which was in agreement with previous studies [9, 43, 45]. Immunocytochemical staining revealed that the red fluorescence intensity in the cytoplasm was higher, while western blot analysis showed more HO-1 expression in Ad/HO-1/BMMSCs than in BMMSCs and in Ad/BMMSCs, indicating that the HO-1 gene was successfully overexpressed in the cytoplasm of Ad/HO-1/BMMSCs.…”
Section: Discussionsupporting
confidence: 93%
“…Despite the lack of enough in vivo tracking evidence to support any of those views, some articles showed new strategies aiming at prolonging the survival of MSCs in an adverse environment. P2 hBM-MSCs genetically-modified to transiently express cytoprotective factors (i.e., heme oxygenase-1 or nuclear factor erythroid-2 related factor 2), by using adenoviral vectors, were able to survive better in hypoxic and oxidative-stress conditions [86,87].…”
Section: Strategies To Increase Mscs Migratory Survival and Prolifermentioning
confidence: 99%
“…Stem cells genetically combined with HO-1 using Adenovirus vector improved the success of stem cell transplantation. HO-1 has shown cytoprotective effects in mesenchymal stem cells by preventing hypoxia and oxidative stress damage besides retention of the differentiation properties [56].Furthermore ischemia/reperfusion induced renal injury during transplantation was prevented by adenovirus mediated HO-1 delivery [57]. Diabetic mice treated with adenoviral vectors containing HO-1 showed increase in wound healing and neovascularization [58].Recombinant adeno-associated virus (rAAV) offers safe, effective and long term therapy with minimum deleterious effect on host cell and non-immunogenicity making the delivery of HO-1 more effective.…”
Section: Viral Vector Based Ho-1 Gene Transfermentioning
confidence: 99%